Mission of a University in the Society: Formation of a University Tradition and Modern Challenges - Zayachuk, Yuliya; Kovalska, Olena (Pedagogical Discourse, 2020)
This article presents the analysis of the key aspects of the formation of a mission of a university as a scientific, pedagogical, and social institution in different historical periods, in current times and in the future. It also reveals that socio-historical transformations of a university and society are interrelated. It is stated that a university as an institution has a multifaceted mission. The aspects of this mission are research, teaching and service. Other concepts were added to these ones in accordance with social requirements at different times. The change in the interpretation of a university’s mission from its initial understanding as the production of “light of knowledge that an educated person sees in front of himself or herself” to its perception in the twentieth century as “big business” that creates benefits for society has been examined. It is emphasized that an important milestone in the history of a university as an institution was the reform of German cultural leader and thinker W. von Humboldt. His research university model, based on the integration of research and teaching, on the principles of freedom of teaching and freedom of learning, has seriously influenced the development of higher education worldwide and has become a prerequisite for current higher education reform. The article reveals the author’s concepts of a mission of a university of famous intellectuals and influential researchers H. Newman, A. Flexner, K. Jaspers, T. Veblen, C. Kerr, J. Ortega-y-Gasset. It is highlighted that the main issues to characterize the activities of a university are issues of freedom that is research, academic, spiritual, and political freedom. Special emphasis is also placed on the latest concepts of universities namely the concept of the world-class research university of the XXI century by Prof. P. Altbach and model of Entrepreneurial University by Prof. B. Clark, which will work in the conditions of growing competition between higher education institutions as well as in the conditions of emergence of the principle of their orientation to labor market. The article examines the issue of current rethinking of a university mission in accordance with new, complex tasks set by time, and risks for current educational space. The prospects for the development of the idea of a university in the educational processes of the XXIst century are outlined.